2009
DOI: 10.1016/j.jcrs.2009.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental setup to determine the pulse energies and radiant exposures for excimer lasers with repetition rates ranging from 100 to 1050 Hz

Abstract: Higher-repetition-rate excimer lasers require increased radiant exposure. Further experimental studies should be performed to determine the relevance of spatial and temporal spot positioning, ablation-plume dynamics, and temperature increases during high-repetition-rate laser treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…A pulse energy level of 0.67 mJ was specified as a standard value for AMARIS low fluence, representing a factor of 2 in the overall range covered. Laser systems with up to ∼2-mJ pulse energy are available, 35 however, such a high metric has not been covered in our tests and related extrapolations based on our results should be made with caution, although 1.33 mJ of pulse energy in a 0.54-mm spot size represents the upper limit of energy density (∼500 mJ∕cm 2 ) in refractive surgery. A maximum change in peak corneal temperature of 6.85°C and a range of 1.55°C were observed with the controlled local frequency.…”
Section: Pulse Energymentioning
confidence: 89%
“…A pulse energy level of 0.67 mJ was specified as a standard value for AMARIS low fluence, representing a factor of 2 in the overall range covered. Laser systems with up to ∼2-mJ pulse energy are available, 35 however, such a high metric has not been covered in our tests and related extrapolations based on our results should be made with caution, although 1.33 mJ of pulse energy in a 0.54-mm spot size represents the upper limit of energy density (∼500 mJ∕cm 2 ) in refractive surgery. A maximum change in peak corneal temperature of 6.85°C and a range of 1.55°C were observed with the controlled local frequency.…”
Section: Pulse Energymentioning
confidence: 89%
“…A patient treated after repair of the laser electrodes showed no central island, demonstrating the capability of the excimer laser calibration system for predicting the beam profile accurately and subsequently calibrating the system accordingly. Mrochen et al 2 performed a study on freshly enucleated bovine corneas and PMMA plates to evaluate the influence of the dynamics of the laser ablation process, including the pulse energies and radiant exposures. The shot pattern for the myopic correction was maintained during all experiments, and the pulse laser energy was adjusted to achieve equal ablation depths for all repetition rates.…”
Section: Polymethylmethacrylatementioning
confidence: 99%
“…Both materials follow a Beer-Lambert law in the range of fluences used in refractive surgery, and the number of incubation pulses (that is quantified as the number of the first pulses that do not contribute to ablation depth) 5 is <4 in PMMA and 2 in Filofocon A, above 140 mJ∕cm 2 . Above 40 pulses for Filofocon A and 70 pulses for PMMA, ablation threshold and effective absorption coefficients can be considered constant (ablation threshold ¼ 90 mJ∕cm 2 and effective absorption coefficients ¼ 36;000 cm −1 , for Filofocon A, and ablation threshold ¼ 67 mJ∕cm 2 and effective absorption coefficients ¼ 52;000 cm −1 for PMMA, respectively). It was concluded that the absence of ablation artifacts (central islands), a lower number of incubation pulses, a lower pulsenumber dependence of the ablation threshold, and a good correspondence between effective absorption coefficient and the absorption coefficient alpha estimated from spectroscopic measurements make Filofocon A a more appropriate material than PMMA for experimental models in refractive surgery and for calibration of clinical lasers.…”
Section: Filofocon Amentioning
confidence: 99%
“…Bei Photoablation mit hoher Repetitionsrate könnte der Gewebeabtrag pro Laserpuls aufgrund eines Abschirmungseffekts durch die bei der Verdampfung des Gewebes entstehende Gaswolke im Verlauf der Behandlung reduziert werden [9]. Wir konnten durch die Untersuchungen an PMMA bestätigen, dass sich bei dem von uns untersuchten Lasersystem die Effizienz bei den beiden Ablationsfrequenzen nicht unterscheidet.…”
Section: Diskussionunclassified
“…In der letzten Zeit wurden Excimer-Laser mit hohen Repetitionsraten kommerziell verfügbar gemacht. Es besteht jedoch die Sorge, dass die Photoablation bei einem Anstieg der Ablationsfrequenz infolge photochemischer oder photothermischer Einflüsse negativ beeinflusst wird [9].…”
Section: Introductionunclassified